2007
DOI: 10.1037/0893-164x.21.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Condom use with a casual partner: What distinguishes college students' use when intoxicated?

Abstract: Determining alcohol's precise role in sexual risk taking has proven to be an elusive goal. Past research has produced mixed results, depending on characteristics of individuals, their partners, and the situation, as well as how the link between alcohol consumption and sexual behavior was assessed. In this study, cross-sectional predictors of the frequency of condom use were examined for 298 heterosexual college students at a large urban university. In hierarchical multiple regression analyses that controlled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 66 publications
(116 reference statements)
8
46
3
Order By: Relevance
“…Gender differences in self-protective sexual behavior may reflect dyadic power imbalances that limit women's ability to negotiate safer sex, 54 particularly in drinking situations that undermine self-protective strategies. 46,52 While some previous studies have failed to find a significant link between alcohol use and unprotected sex, 17 others have found that the connection between drinking and condom use is to some extent conditioned by gender. 19,54,59 However, in the present analysis, no gender/ AmED interaction was found for any of the three sexual risktaking outcomes; the relationships between AmED use and sexual risk-taking were robust across gender.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gender differences in self-protective sexual behavior may reflect dyadic power imbalances that limit women's ability to negotiate safer sex, 54 particularly in drinking situations that undermine self-protective strategies. 46,52 While some previous studies have failed to find a significant link between alcohol use and unprotected sex, 17 others have found that the connection between drinking and condom use is to some extent conditioned by gender. 19,54,59 However, in the present analysis, no gender/ AmED interaction was found for any of the three sexual risktaking outcomes; the relationships between AmED use and sexual risk-taking were robust across gender.…”
Section: Discussionmentioning
confidence: 98%
“…3,11 Drinking increases the likelihood of indiscriminate sexual activity, including sex with a casual, unplanned, and/or high-risk partner. [12][13][14][15][16] Although the relationship between drinking and condom use is complex, 12,17,18 alcohol use may in some instances reduce the odds of using barrier protection against pregnancy or STIs. 19 In 2011, fewer than two-thirds of sexually active college students reported condom use during their most recent intercourse, and one in six alcohol-using students reported having had unprotected sex as a consequence of his or her drinking in the past 12 months.…”
mentioning
confidence: 99%
“…However, in a study of women only, Cooper and Orcutt (2000) found that drinking and condom use were more common with casual partners. In a recent study of college students' risky sexual behavior with casual partners, Abbey et al (2007) found that condom use when sober was the strongest predictor of condom use when drinking.…”
Section: Differences In Substance Use and Risky Sex Based On Partner mentioning
confidence: 99%
“…59 Finally, a study of college students found that those who were higher in self-efficacy were more likely to use condoms while drunk than those lower on this domain. 52 The purpose of the current manuscript is to explore how established cognitive predictors of risky sexual behavior may moderate the association between situational factors and unprotected sex using a cross-sectional Partner-Level Model (PLM); if moderation is found, it suggests that approaches to positively influence cognitions may help sever the association between situational factors and unhealthy outcomes. In our sample of very low-income, African American adolescents, we used the sexual partnership, rather than the individual, as the unit of analysis.…”
Section: Information Motivation and Behavioral Skills (Imb)mentioning
confidence: 99%
“…15 The IMB Model draws on the tenets of Social Cognitive Theory 49 and Theory of Reasoned Action, 50 and it asserts that the fundamental determinants of engaging in behaviors that prevent HIV acquisition are the combined effects of having: (a) HIV-related information and prevention knowledge, (b) motivation to become/stay safer, and (c) necessary skills to engage in prevention behaviors, including self-efficacy to use condoms. 51 The literature on heterosexual youth and adults generally supports the association between the components of the IMB model and sexual risk behavior in both observational studies 16,[51][52][53][54][55][56] and tests of interventions. 57,58 However, evidence suggests that motivation and behavioral skills may play a more proximal role in influencing sexual risk than HIVrelated information.…”
Section: Information Motivation and Behavioral Skills (Imb)mentioning
confidence: 99%